1975
DOI: 10.1128/jcm.1.2.165-170.1975
|View full text |Cite
|
Sign up to set email alerts
|

Stability of pathogenic colony types of Neisseria gonorrhoeae in liquid culture by using the parameters of colonial morphology and deoxyribonucleic acid transformation

Abstract: This investigation describes the surveillance of the colonial stability of the pathogenic type 1 from the gonococcal strain F62 to the nonvirulent types 3 and 4 in different liquid media. The maintenance of the colony types was monitored by the parameters of colonial morphology and deoxyribonucleic acid-mediated transformation. During growth in a complex medium, Mueller-Hinton broth, only 46.7% of the gonococcal population remained as type 1 after 12 h. The greatest change in the type 1 colony-forming units co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
1

Year Published

1976
1976
1979
1979

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
1
7
1
Order By: Relevance
“…These experiments demonstrate that N. gonorrhoeae can be genetically transformed from a nonpilated T4 clonal type to a pilated Ti or T2 morphology by DNA extracted from pilated gonococci. The transformation was sensitive to DNase, and, distinguished from the results reported by others (14,20,35) in attempts to transform T4 cells, under optimal conditions, the rate approximated 2% and was rarely less than 1%. The phenotypically Ti and T2 in addition to colonial morphology (16) possessed pili (40) and could undergo DNA-mediated transformation (35).…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…These experiments demonstrate that N. gonorrhoeae can be genetically transformed from a nonpilated T4 clonal type to a pilated Ti or T2 morphology by DNA extracted from pilated gonococci. The transformation was sensitive to DNase, and, distinguished from the results reported by others (14,20,35) in attempts to transform T4 cells, under optimal conditions, the rate approximated 2% and was rarely less than 1%. The phenotypically Ti and T2 in addition to colonial morphology (16) possessed pili (40) and could undergo DNA-mediated transformation (35).…”
Section: Discussioncontrasting
confidence: 64%
“…There are numerous reports in the literature that pilation, colonial morphology (Ti and T2), and virulence are linked (2,14,20,30,34,35,38). The following study, using transformation as a tool, was undertaken to clarify the possible association of pilation with colonial morphology and virulence.…”
mentioning
confidence: 99%
“…Most of these variations seem to occur after active growth, either in individual colonies or in liquid cultures, has ceased. This point has also been noted by others (10), but no explanations for this observation have been forthcoming. To elucidate the mechanisms for these variations, we initially tried to ascertain whether they might have a genetic basis.…”
Section: Discussionsupporting
confidence: 50%
“…The growth curves of Ti and T4 suggested that growth of gonococci can be followed with both viable CFU and absorbance readings. Although previous investigators have followed growth of N. gonorrhoeae with readings from a Klett-Summerson colorimeter (6,7,9), our experience has been that such readings often are irreproducible because of differences in machines and filter types. For this reason, absorbance readings at a specific wavelength of 450 nm, accompanied by counts of viable CFU, provide a more accurate and consistent measurement of growth of Ti and T4 bacteria.…”
Section: Resultsmentioning
confidence: 99%